MEMPROGRAMKAN AKSES PEMBIAYAAN SYARIAH BAGI USAHA MIKRO KECIL DAN MENENGAH DESA PURASEDA, KECAMATAN LEUWILIANG, BOGOR - Rully Trihantana; Miftakhul Anwar; Adjriel Hedriawan (SAHID DEVELOPMENT JOURNAL, 2022)
Efforts in alleviating poverty can be done, among others, by breaking the chain of poverty itself,for example by providing broad access to financing sources for Micro, Small and MediumEnterprises (MSMEs) which are applied by Islamic banking and Islamic microfinance institutions.One source of funding is sharia-based banking and financial institutions. Islamic banking andSharia Microfinance Institutions (LKMS) including in this case Baitul Mal wat Tamwil (BMT)have an important role in the development of MSME actors, especially in terms of funding andbusiness capital. With this in mind, access to sharia financing was programmed for MSMEs inPuraseda Village, Leuwiliang District, Bogor.